Potential of Bacillus sp. from Kebun Raya Liwa as a Producer of Indole Acetic Acid (IAA) Hormone - Fadlina Athfin; Kusuma Handayani; Wawan A. Setiawan; C. Nugroho Ekowati (Universitas Islam Indonesia, 2023)
Kebun Raya Liwa’s soil has the potential to allow for a population of microorganisms such as the Bacillus sp. Bacillus sp. Kebun Raya Liwa are known to produce phytohormones that have the potential to help plant growth and development, one of which is the hormone Indole Acetic Acid (IAA). This study aims to determine the potential of Bacillus sp. from the soil of Kebun Rawa Liwa in producing IAA hormones. The research method included taking soil samples, preparing Nutrient Agar (NA) medium, measuring soil pH samples, isolating soil bacteria, purifying and characterizing Bacillus sp., preparing IAA standard curves, and testing the potency of Bacillus sp. IAA production was carried out in two ways, namely measuring the content of IAA with the addition of tryptophan and without the addition of tryptophan. IAA concentration was measured using a spectrophotometer with a wavelength of 520 nm. The data obtained is presented in tabular form. The isolation results obtained 10 isolates that were able to produce IAA hormone with and without tryptophan. The highest IAA production without tryptophan was isolate BP 5 with a concentration of 1.18 ppm, and the isolate that was able to produce the highest IAA with tryptophan was isolate BP 13 with a concentration of 3.90 ppm. This indicates that the isolate Bacillus sp. from the soil rhizosphere Kebun Raya Liwa can produce IAA hormones.